1908 Management of Pulmonary Hypertension after Paediatric Cardiac Surgery. (October 2012) - Wildeboer, GJ; Ponne, E; Geerts, H
Abstract : Introduction: Treatment of pulmonary hypertension in children has significantly improved over the years. The Beatrix Children's Hospital serves as the nationwide referral center for these children. Of importance, pulmonary hypertension occurs in a considerable proportion of patients after cardiac surgery. Our paediatric intensive care unit admits approximately 180 patients annually after cardiac surgery. About 5% of these children develop pulmonary hypertension. Its occurrence may significantly affect the post-operative disease course during the first 72 hours of PICU stay. Aim: The provide insight into early recognition and management of pulmonary hypertension after cardiac surgery. Methods: We have developed nursing protocols describing how to monitor and interpret haemodynamic parameters, and how to interpret laboratory and roentgenologic investigations. Special attention is paid towards the clinical appearance of the patient. Next to this, supportive tools such as nitric oxide and high-frequency oscillatory ventilation (HFOV) are inevitable. Results: A protocolized approach allows us to recognize complications after paediatric cardiac surgery early during PICU stay. As a consequence, early management is possible. Nitric oxide and HFOV are used as a supportive intervention for managing pulmonary hypertension. Conclusion: A protocolized approach allows us to recognize complications after paediatric cardiac surgery early during PICU stay.